The Effect Of Capital Intensity And Profitability On Tax Planning With Board Independence As A Moderating Variable - Leynavira Safitri; Bani Binekas (UNIVED Press, 2026)
Tax planning is a strategic issue as governments increasingly rely on corporate tax revenue to finance development. This study examines the effects of capital intensity and profitability on corporate tax planning and evaluates the moderating role of board independence. Using a quantitative causal-comparative design, the study analyzes food and beverage companies listed on the Indonesia Stock Exchange during 2020–2024. Firms were selected through purposive sampling based on audited financial statements, positive earnings, and complete governance disclosures. Secondary data were analyzed using multiple linear regression and moderated regression analysis. The results indicate that capital intensity and profitability do not significantly affect tax planning, and board independence does not moderate these relationships. Nevertheless, the overall model is statistically significant, suggesting that tax planning may be influenced by other organizational or institutional factors. This study contributes to the literature by reassessing the role of financial and governance variables in tax planning research and offers practical insights for regulators and managers to strengthen governance quality and ensure tax strategies remain efficient, compliant, and sustainable.